ChemInform Abstract: Trigonal Planar [HgSe3]4‐ Unit: A New Kind of Basic Functional Group in IR Nonlinear Optical Materials with Large Susceptibility and Physicochemical Stability. Issue 38 (September 2016) - Li, Chao; Yin, Wenlong; Gong, Pifu; Li, Xiaoshuang; Zhou, Molin; Mar, Arthur; Lin, Zheshuai; Yao, Jiyong; Wu, Yicheng; Chen, Chuangtian
Abstract: Single crystals of BaHgSe2 are grown from an equimolar mixture of HgSe and BaSe (evacuated silica tubes, 850 °C, 72 h).